Studi Intensitas Cahaya Matahari Dengan Data Logger Untuk Efektiv Penempatan Panel Surya - Asnal Effendi; Arfita Yuana Dewi; Siti Amalia; Dedy Alfianto (Journal of Electrical Power Control and Automation (JEPCA), 2021)
Renewable energy is energy produced from natural sources, such as light, wind, rain, tidal currents, and geothermal, which is renewable or can naturally reappear after being used. In this study, a study of the effectiveness and efficiency of power plants in certain locations. For this reason, it is necessary to design a tool in the form of a data logger that is used to collect parameter data such as light intensity, electric voltage, electric current, power, temperature, humidity, wind speed, and others. The placement of the data logger will help in the basic test of the feasibility of using energy sources later. Data logger is a system that can record automatic parameters of current, voltage, power on solar panels and automatically record conditions of temperature, humidity in the solar panel. The results of logger data on light intensity for a more efficient placement of solar panels occur at location 1 Beach behind Kmpus UBH 1, where at that location has an average light intensity of 798.24 Cd.